A new species of Leptolalax (Anura: Megophryidae) from Mizoram, North-eastern India - Sengupta, S.; Sailo, S.; Lalremsanga, H.T; Das, A.; Das, I. (Zootaxa, 2010)
A new species of megophryid frog of the genus Leptolalax is described from the Tamdil wetlands of Mizoram State, north-eastern India. L. tamdil new species, is compared with congeners from India and other parts of south-east Asia. The new species is diagnosable in showing the following combination of characters: SVL 32.3 mm in the only male and 31.8 mm in the only female known; dorsum tuberculate; eyelids with tubercles; tympanum and supratympanic fold distinct; supratympanic fold extending to posterior edge of tympanum; macroglands, including preaxillary, pectoral, femoral and ventrolateral glands present; Finger II > I; toe tips not dilated, bearing dermal fringes; relatively long hind limbs, with heels in contact when limbs are held perpendicular to body; dorsum with dark blotches; flanks with small dark blotches; dark tympanic mask present; venter pale; labial bars present and limbs with dark cross-bars.